Kajian Struktur Pertunjukan Tari Gandhong di Desa Bangun Kecamatan Munjungan Kabupaten Trenggalek - Femilia Kristian Arum Sari; Setyo Yanuartuti (Universitas Negeri Medan, 2020)
Gandhong Dance is a dance that was created for the ritual procession at a ritual ceremony performed at Coban Wono Asri which is located in Bangun Village, Munjungan District, Trenggalek Regency. The focus of the problem in this paper is that Gandhong Dance has a performance structure that is unique and different from the others, so this paper aims to examine more deeply the performance structure of Gandhong Dance. In order to approach this problem, Ben Suharto's translation of Jackquline Smith (1985) is used as a theoretical reference, that the structure is a form consisting of forms and forming elements that are interrelated according to its function and are inseparable in a unified form. Data were collected through observation, interviews and documentation and were analyzed using a qualitative approach. This study concludes that Gandhong Dance, in one package of this Gandhong Dance performance there is a separate sub-theme in which there are only small themes forming the sub-theme.